Application of the novel ETS-10/water pair in cyclic adsorption heating processes: Measurement of equilibrium and kinetics properties and simulation studies. (5th August 2015) - Pinheiro, Joana M.; Valente, Anabela A.; Salústio, Sérgio; Ferreira, Nelson; Rocha, João; Silva, Carlos M.
Abstract: The ETS-10/water pair was explored for the first time for cyclic adsorption heating purposes, with modelling and simulation studies. Measurements of water adsorption equilibrium properties were carried out, and, for the first time, the effective thermal conductivity and specific heat capacity of ETS-10 were measured. The experimental results were used for the modelling and simulation of an adsorption heating unit. A model was developed, which contemplates adsorption equilibrium, one-dimensional heat and mass transfer in the bed, heat transfer in the external film, and intraparticle mass transport. From the numerical simulations, the coefficient of performance (COP) and specific heating power (SHP) were calculated, which allowed evaluating the heating performance of the adsorption unit. The bed thickness, adsorbent regeneration temperature, and heating thermal fluid temperature influence considerably the cycle time and cyclic adsorption loading swing, thus impacting on COP and SHP. For three simulated cycles differing in bed thickness, COP values in the range 1.36–1.39 were obtained, which are close to the estimated ideal value of 1.41; the corresponding SHP ranged from 934 to 249 W kgs −1 . Based on sensitivity studies, a good compromise is required between the bed thickness, regeneration temperature, and the heating fluid temperature in order to meet superior performances of the system. Graphical abstract: Highlights: Modelling & simulation of a cyclic adsorption heating unit using novel ETS-10/water pair. Equilibrium isotherms and thermophysical data of ETS-10 measured here for the first time. COP = 1.36 and SHP = 934 W k g s − 1 were obtained for bed thickness of 2 mm. The overall heating performance was highly influenced by geometric/operating conditions.